Peningkatan Kemampuan Kognitif (Konsep Bilangan) Anak Melalui Media Kartu Angka Matching - Elza Novrianti; Ela Pebriani; Lydia Margaretha (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to enhance children's cognitive abilities—specifically regarding number concepts—through the use of matching number cards in early childhood education (PAUD). The study employs the Classroom Action Research (CAR) method, conducted over two cycles; each cycle comprises the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 12 children from Group B (aged 5–6 years). Data collection was carried out through observation and documentation, while data analysis utilized quantitative descriptive analysis with percentages. The results indicate that the use of matching number cards can improve children's cognitive abilities in recognizing number concepts. This improvement is evident in the percentage results across each cycle. In Cycle I, Meeting 1, the children's cognitive ability score was 41.66% (categorized as